Simulações de líquidos super-resfriados via dinâmica molecular - Gonçalves, Luis Gustavo Vieira (2012)
This work presents the study of two models of glass-forming liquids using molecular dynamics simulations. The first model aims to analyze the effects on glassy dynamics which allow the enhancement of the glass formability on metallic glass formers. The Pd45Ni55 binary alloy and the Pd35Ni55Pt10 ternary one are modeled via the Embedded Atom method interaction potential, which is known to efficiently reproduce mechanical and structural properties in metallic compounds. Results of the dynamic susceptibilities indicate that the addition of Pt to the binary alloy favors its glass formability, given that such addition allowed the enhancement of collective dynamics. The conclusion is that the change on the medium range structure influences the increased collectivity found in the system. The second model aims to analyze the diffusion mechanisms and characterize the glassy dynamics of a supercooled network glass-forming liquid. The material to be modeled is lithium disilicate, which is a well studied material due to its versatility and applicability in both industry and academia. The Buckingham interaction potential is employed to model lithium disilicate in liquid and glassy phases. Results of dynamical and structural properties show excellent agreement with available experimental data. However, the decoupling between diffusion and relaxation, which is equivalent as the break-down of the Stokes-Einstein relation, occurs far above the melting temperature calculated via simulation, in strong disagreement with experimental observations. Nevertheless, dynamic heterogeneities present in the supercooled liquid are well characterized through the analysis of the distribution of displacements and atomic visualizations.